Role of Yemen higher education institutes in rebuilding the post-war Yemen - Al-haimi, Basheer; Daing Nasir, Ibrahim; Mohd Rashid, Ab Hamid; Hujainah, Fadhl (Inderscience Enterprises Ltd., 2021)
Higher education institutes (HEIs) have exerted a significant influence on the rebuilding of countries affected by conflicts. These institutes operate as catalysts of healing in conflict-affected societies. The ongoing war in Yemen has resulted in negative economic and social consequences. This study aims to examine the role of Yemen HEIs (YHEIs) in the reconstruction of post-war Yemen. The study discusses how HEIs can contribute in rebuilding Yemen by addressing concerns regarding peace-building, social fabric healing, and economic rebuilding. A qualitative method of data collection involving the use of in-depth interview was employed in gathering information from Malaysian and Yemeni academics. The results of the interview indicated that YHEIs can play a crucial and major role in rebuilding the country in terms of peace-building, social fabric healing, and economic growth. Peace-building and social fabric can be accomplished through various ways related to teaching and learning, applied research, societal engagement, and civic programs. Economic growth also can be achieved through different aspects such as focusing on capacity building, collaborating with various sectors, gaining-brain, producing skillful workers and international partners.